If it's not what You are looking for type in the equation solver your own equation and let us solve it.
28=6g-8
We simplify the equation to the form, which is simple to understand
28=6g-8
We move all terms containing g to the left and all other terms to the right.
-6g=-8-28
We simplify left and right side of the equation.
-6g=-36
We divide both sides of the equation by -06 to get g.
g=6
| 2x-20=x/2+10 | | 48x^3-12x^2-6x=0 | | 54-2x=10x-18 | | 7-(2x-8)=5-3x | | 2x^2=-2x+5 | | 2x=x/2+10 | | 10x+5x-2x=69 | | 208-3x=x+(x+1)+(x+2)+(x+3)+(x+4)-50 | | 3x+36=10x-48 | | y=25x-7 | | x^4+4x^3+1=0 | | 8(m-1)-7(m+3)=-29 | | 3x+108=9x-12 | | -5x-3(-x+1)=7 | | N+6=-44 | | 107-7x=29x+23 | | 2x/4=6*3 | | 150-5x=22x+18 | | -6x-6(-4x-11)=12 | | 12x^2-40=17x | | (x-7)=(x+3) | | y=-4(-2)-5 | | 23=m-9 | | 7.31=d+3.31 | | 5x+2x=55 | | 2-7x=1-6x | | x^2-15*8= | | x^3-10x^3+21x=0 | | 12x+11=119 | | y=-2-2-3-2-4 | | (6*2-4)/2 | | x-9y=-21 |